Need for Intensive Nutrition Care After Bariatric Surgery: Is Mini Gastric Bypass at Fault?. (9th March 2016) - Bétry, Cécile; Disse, Emmanuel; Chambrier, Cécile; Barnoud, Didier; Gelas, Patrick; Baubet, Sandrine; Laville, Martine; Pelascini, Elise; Robert, Maud
Abstract : Severe nutrition complications after bariatric surgery remain poorly described. The aim of this case series was to identify specific factors associated with nutrition complications after bariatric surgery and to characterize their nutrition disorders. We retrospectively reviewed all people referred to the clinical nutrition intensive care unit of our university hospital after bariatric surgery from January 2013 to June 2015. Twelve persons who required artificial nutrition supplies (ie, enteral nutrition or parenteral nutrition) were identified. Seven persons underwent a "one‐anastomosis gastric bypass" (OAGB) or "mini gastric bypass, " 2 underwent a Roux‐en‐Y gastric bypass, 2 had a sleeve gastrectomy, and 1 had an adjustable gastric band. This case series suggests that OAGB could overexpose subjects to severe nutrition complications requiring intensive nutrition care and therefore cannot be considered a "mini" bariatric surgery. Even if OAGB is often considered a simplified surgical technique, it obviously requires as the other standard bariatric procedures a close follow‐up by experimented teams aware of its specific complications.